ANTHOCYANIN LEVELS AND ANTIOXIDANT ACTIVITY OF TORTILLA PURPLE SWEET POTATO (Ipomoea batatas L) - Fitriani Basrin; Miming Berlian; Yuanita Indriasari; Ramadhani Chaniago (AGROLAND The Agricultural Sciences Journal (e-Journal), 2021)
Purple sweet potato is a source of anthocyanins that function as antioxidants, antimutagenic, and anti-carcinogenic so that it has the potential to be processed into various functional food products. The stability of anthocyanin levels in the product is greatly influenced by temperature during processing, where the use of high temperatures will damage and reduce anthocyanin levels. This research was conducted to determine the effect of processing and combination of raw materials on anthocyanin levels and antioxidant activity of tortilla products made from a combination of purple sweet potato (Ipomoea batatas L) and cassava. The research design used a completely randomized design, with the object of research being tortillas made from purple sweet potato obtained from Palolo District, Sigi Regency, Central Sulawesi Province, combined with cassava obtained from the local market in Palu City, Central Sulawesi Province. The results showed that the anthocyanin levels of tortilla products varied from 5% (P1) to 19.63% (P5). There was a very significant decrease in anthocyanin levels around 68.26 - 91.91%. The amount of antioxidant activity was measured by IC50, wherefrom the research it was known that the IC50 value of tortilla products ranged from 242.68 to 155.66 µg / ml which indicated that the antioxidant activity of tortilla products was weak and even almost inactive. Based on the results of the study, it is indicated that the processing of purple sweet potatoes into tortillas is not appropriate because the processing is predominantly using high temperatures so that it can damage the anthocyanin content and reduce antioxidant activity.